Biomodulatory Treatment With Azacitidine, All-trans Retinoic Acid and Pioglitazone Induces Differentiation of Primary AML Blasts Into Neutrophil Like Cells Capable of ROS Production and Phagocytosis - Klobuch, Sebastian; Steinberg, Tim; Bruni, Emanuele; Mirbeth, Carina; Heilmeier, Bernhard; Ghibelli, Lina; Herr, Wolfgang; Reichle, Albrecht; Thomas, Simone (Frontiers in Pharmacology, 2018)
Effective and tolerable salvage therapies for elderly patients with chemorefractory acute myeloid leukemia (AML) are limited and usually do not change the poor clinical outcome. We recently described in several chemorefractory elderly AML patients that a novel biomodulatory treatment regimen consisting of low-dose azacitidine (AZA) in combination with PPARgamma agonist pioglitazone (PGZ) and all-trans retinoic acid (ATRA) induced complete remission of leukemia and also triggered myeloid differentiation with rapid increase of peripheral blood neutrophils. Herein, we further investigated our observations and comprehensively analyzed cell differentiation in primary AML blasts after treatment with ATRA, AZA, and PGZ ex vivo. The drug combination was found to significantly inhibit cell growth as well as to induce cell differentiation in about half of primary AML blasts samples independent of leukemia subtype. Notably and in comparison to ATRA/AZA/PGZ triple-treatment, effects on cell growth and myeloid differentiation with ATRA monotherapy was much less efficient. Morphological signs of myeloid cell differentiation were further confirmed on a functional basis by demonstrating increased production of reactive oxygen species (ROS) as well as enhanced phagocytic activity in AML blasts treated with ATRA/AZA/PGZ. In conclusion, we show that biomodulatory treatment with ATRA/AZA/PGZ can induce phenotypical and functional differentiation of primary AML blasts into neutrophil like cells, which aside from its antileukemic activity may lower neutropenia associated infection rates in elderly AML patients in vivo. Clinical impact of the ATRA/AZA/PGZ treatment regimen is currently further investigated in a randomized clinical trial in chemorefractory AML patients (NCT02942758).